Bicentenario : Echoes of Independence 200 years later (Sharjah Museums Department, 2011)
Exhibition catalog. Participating artists: Benito Mieses, Ivan Dario Hernandez, Luis Villamizar, Morella Jurado, Saul Huerta, Ender Cepeda, Beatriz Blanco. This exhibition highlights a pivotal experience in the history of the Bolivarian Republic of Venezuela, the 200th anniversary of the success its heroic war of independence from Spain. The Ministry of Popular Power for Foreign Affairs of the Bolivarian Republic of Venezuela, the organiser of the exhibition, affirms the primary aim is to 'build a safe and stable bridge with the Middle East, starting from the regenerated process that our people are experiencing where revolutions generated different forms of art and practice, as well as other means to approach life through diversified aesthetic experiences, bringing together and integrating elements and metaphors that go beyond the differences between the elite and popular, sconomic and cultural, and the ancient and the modern.'
English; Arabic
Keywords: N4390-5098 Exhibitions; Venezuela